Inflammatory response and parasite regulation in acute toxoplasmosis: the role of P2X7 receptor in controlling virulent atypical genotype strain of Toxoplasma gondii - Prado-Rangel, Thuany; Moreira-Souza, Aline Cristina Abreu; da Silva, Sthefani Rodrigues Batista; Barboza-Araujo, Thais; Castro-Junior, Archimedes Barbosa; Ramos, Isalira Peroba Rezende; Takiya, Christina Maeda; Vommaro, Rossiane Claudia; Coutinho-Silva, Robson (Frontiers in Immunology, 2024)
Toxoplasmosis is a globally significant disease that poses a severe threat to immunocompromised individuals, especially in Brazil, where a high prevalence of virulent and atypical strains of Toxoplasma gondii is observed. In 1998, the EGS strain, exhibiting a unique infection phenotype, was isolated in Brazil, adding to the complexity of strain diversity. The P2X7 receptor is critical in inflammation and controlling intracellular microorganisms such as T. gondii. However, its genetic variability can result in receptor dysfunction, potentially worsening susceptibility. This study investigates the role of the P2X7 receptor during acute infection induced by the EGS atypical strain, offering insight into the mechanisms of T. gondii infection in this context. We infected the female C57BL/6 (WT) or P2X7 knockout (P2X7−/−) by gavage. The EGS infection causes intestinal inflammation. The P2X7−/− mice presented higher parasite load in the intestine, spleen, and liver. The absence of the P2X7 receptor disrupts inflammatory cell balance by reducing NLRP3, IL-1β, and Foxp3 expression while increasing IFN-γ expression and production in the intestine. In the liver, P2X7-/- animals demonstrate diminished inflammatory infiltrate within the portal and lobular regions concurrent with an enlargement of the spleen. In conclusion, the infection of mice with the EGS strain elicited immune alterations, leading to acute inflammation and cytokine dysregulation, while the P2X7 receptor conferred protection against parasitic proliferation across multiple organs.